(untitled) (Research, Society and Development, 2021)
In Dentistry, complementary imaging exams aim to provide information that is complementary to the diagnosis, so due to its practicality, the portable x-ray device is increasingly used by dental surgeons to perform intraoral images. Thus, the objective of the present study is to know if the handling of the portable machine is safe for the operator. The present integrative literature review had Bireme, Scielo and Pubmed as a source of research in the search for articles, with research directed to publications that studied the radiation dose to which portable device operators are exposed, at the end of the research 12 articles were selected. During the literary review it was observed that in the execution of the tests, the portable x-ray machines were tested together with phantoms with dosimeters attached or in close proximity to the target areas under test, in order to evaluate the amount of radiation dose to which the professional is exposed. After carefully reading the articles of the selected articles, it was noted that the portable devices emit a dose of radiation below those recommended as an occupational limit, however with great potential for spreading through the mobile nature, having its use indicated for specific occasions, aiming to respect the principle of ALARA. Such a dose can still be reduced with the use of radiation protection measures. It is concluded that these devices are safe to use, but this should be restricted to situations in which a fixed device cannot be used and with additional use of PPE.